Alteplase for Stroke With Unknown Onset Time in Chronic Kidney Disease: A Pooled Analysis of Individual Participant Data. Issue 11 (23rd August 2022) - Miwa, Kaori; Koga, Masatoshi; Jensen, Märit; Inoue, Manabu; Yoshimura, Sohei; Fukuda-Doi, Mayumi; Boutitie, Florent; Ma, Henry; Ringleb, Peter A.; Wu, Ona; Schwamm, Lee H.; Warach, Steven; et al.
Abstract : Background: Although chronic kidney disease (CKD) is associated with worse stroke outcomes, data regarding the influence of CKD on intravenous thrombolysis outcomes are scarce. We sought to assess the efficacy and safety of intravenous thrombolysis for acute ischemic stroke with unknown onset time in patients with CKD. Methods: Patients with an acute stroke of unknown onset time from the EOS trials (Evaluation of Unknown Onset Stroke Thrombolysis) collaboration were evaluated using an individual patient-level database of randomized controlled trials comparing intravenous thrombolysis with placebo/standard treatment. CKD was defined as baseline estimated glomerular filtration rate of <60 ml/min/1.73m 2 Mixed-effect logistic-regression analysis was performed to evaluate treatment effects. A favorable outcome was defined as a modified Rankin Scale score of 0 to 1 at 90 days. Safety outcomes were symptomatic intracranial hemorrhage at 22 to 36 hours and 90-day mortality. Results: Baseline data on renal function were available for 688 of 843 patients. Of these, CKD was present in 146 (21%), including 69 of 351 patients receiving alteplase and 77 of 337 patients receiving placebo/standard treatment. Overall, treatment with alteplase was associated with higher odds of favorable outcome, and CKD did not modify the treatment effect ( P interaction =0.834). A favorable outcome was observed in 31 of 69 (46%) patients with CKD in the alteplase group and in 28 of 77 (36%) patients with CKD in the control group (adjusted odds ratio, 1.19 [95% CI, 0.55–2.58]). Among patients with CKD, symptomatic intracranial hemorrhage occurred in 2 patients (3%) in the alteplase group but in none of the controls ( P =0.133). At 90 days, death was reported in 3 patients (4%) in the alteplase group compared with 2 patients (3%) in the controls ( P =0.539). Conclusions: The present analysis indicates that the benefit of alteplase does not differ between stroke patients with unknown onset time with and without CKD, although the statistical power was lacking to confirm the efficacy in subgroups. This study only applies to mild-to-moderate or predialysis CKD.